ENHANCED PREVENTIVE MAINTENANCE STRATEGY TO OPTIMIZE MAIN ENGINE STARTER SYSTEM PERFORMANCE ON MARINE VESSELS - Nugraha, I Made Aditya; Desnanjaya, I Gusti Made Ngurah; Pramana, Putu Indra (Jurnal Perikanan Unram, 2025)
The starter system is a vital component in the main engine starting process on a ship, so its reliability is an important factor in ensuring smooth sailing operations. This study aims to analyze the effectiveness of implementing preventive maintenance in improving the performance of the main engine starter system on a passenger ship. The study was conducted on the XYZ ship using a descriptive method through direct observation and interviews with the engineer officer. Data obtained included the physical condition of the battery, cable path, solenoid, and internal components of the starter dynamo, then analyzed based on performance parameters before and after preventive maintenance. The results showed several major problems, including heavy starter rotation, rapid battery voltage drop, loose cable connections, and damage to the solenoid. After implementing preventive maintenance such as adding battery water, cleaning terminals, tightening cable connections, and internal maintenance of the starter, there was a significant increase in engine starting speed, battery voltage stability, and starter response. The frequency of previously frequent problems also decreased drastically. The conclusion of this study is that preventive maintenance is proven to be effective in improving starter system performance, reducing the risk of starting failure, and supporting the smooth and safe operation of the ship as a whole. Implementation of scheduled preventive maintenance is recommended to ensure long-term reliability of the starter system.